PLAN DE NEGOCIOS PARA LA IMPLEMENTACIÓN DE PRODUCTOS TURÍSTICOS EN LA FINCA “ANFIGRANJA NANKAIS” DE LA PARROQUIA RURAL LOS ENCUENTROS, CANTÓN YANTZAZA, PROVINCIA ZAMORA CHINCHIPE - Morocho Merino, Evelyn Noelia (2019)
In the los Encuentros rural parish located in Yantzaza canton, the tourism is a activity low developed. For that reason, it was proposed to carry out a Business Plan for the Implementation of Tourism Products in the Anfigranja Nankais "Land, located in Los Encuentros rural parish, Yantzaza canton, Zamora Chinchipe province. For preparating of the research was established as a general objective: Prepare a Business plan for the implementation of tourism products in the farm "Anfigranja Nankais" of the rural parish Los Encuentros, canton Yantzaza, Zamora Chinchipe province, the three specific objectives were propounded: realice a diagnosis of the current situation of the "Anfigranja Nankais" farm of the Los Encuentros rural parish, in which the internal situation of the farm was known. Propose a business plan for tourist products of the "Anfigranja Nankais" Land, located in Los Encuentros parish, which was developed through the definition, promotion and dissemination of the project, technical study, business organization and a financial study. Proposing the strategies for the implementation of the Business Plan of the tourist products of the farm "Anfigranja Nankais" of the Los Encuentros parish, allows to develop the financing and implementation of the business for knowing if it is feasible or not. For the fulfillment of the specific research objectives, the deductive, inductive, analytical and descriptive methods were used. As a techniques were used the survey, interview and direct observation, which allowed to develop the FODA matrix (strengths, opportunities, weaknesses, and threats) of external and internal factors of the land, giving this in turn the matrix of strategic objectives, MINTUR tourist attractions cards and summary cards were used. Regarding the results of the tourism diagnosis, five strategic objectives were obtained, which were elaborated in the business plan proposal with adequate infrastructure for the provision of tourist services. Being a fundamental tool for the start-up of the business; therefore, the initial investment for the execution of the project could be established at $$185.646,01; the execution of the project is feasible and feasible. After having carried out the research, it is concluded that the "Anfigranja Nankais" land, has characteristics to carry out tourist activities, which will allow generating new jobs and improving tourism activity and generating a business or entrepreneurship opportunity for its inhabitants.